Insights into the Enhanced Cycle and Rate Performances of the F‐Substituted P2‐Type Oxide Cathodes for Sodium‐Ion Batteries. Issue 19 (29th March 2020) - Liu, Kai; Tan, Susheng; Moon, Jisue; Jafta, Charl J.; Li, Cheng; Kobayashi, Takeshi; Lyu, Hailong; Bridges, Craig A.; Men, Shuang; Guo, Wei; Sun, Yifan; Zhang, Jinli; et al.
Abstract: A series of F‐substituted Na2/3 Ni1/3 Mn2/3 O2− x F x ( x = 0, 0.03, 0.05, 0.07) cathode materials have been synthesized and characterized by solid‐state 19 F and 23 Na NMR, X‐ray photoelectron spectroscopy, and neutron diffraction. The underlying charge compensation mechanism is systematically unraveled by X‐ray absorption spectroscopy and electron energy loss spectroscopy (EELS) techniques, revealing partial reduction from Mn 4+ to Mn 3+ upon F‐substitution. It is revealed that not only Ni but also Mn participates in the redox reaction process, which is confirmed for the first time by EELS techniques, contributing to an increase in discharge specific capacity. The detailed structural transformations are also revealed by operando X‐ray diffraction experiments during the intercalation and deintercalation process of Na +, demonstrating that the biphasic reaction is obviously suppressed in the low voltage region via F‐substitution. Hence, the optimized sample with 0.05 mol f.u. −1 fluorine substitution delivers an ultrahigh specific capacity of 61 mAh g −1 at 10 C after 2000 cycles at 30 °C, an extraordinary cycling stability with a capacity retention of 75.6% after 2000 cycles at 10 C and 55 °C, an outstanding full battery performance with 89.5% capacity retention after 300 cycles at 1 C. This research provides a crucial understanding of the influence of F‐substitution on the crystal structure of the P2‐type materials and opens a new avenue for sodium‐ion batteries. Abstract : In this cathode system, F‐substitution induces Ni/Mn cation redistribution and disrupts Na ordering. The underlying charge compensation mechanism indicates a partial reduction of Mn 4+ to Mn 3+ upon F‐substitution and the reduced Mn ions participate in the redox reaction process during cycling, contributing to an increase in discharge specific capacity.